Facile synthesis of hollow microspherical YPO4: Eu3+/Tb3+ using polystyrene spheres as sacrificial template and its photoluminescent properties. (1st May 2018) - Gao, Yu; Feng, Jinzhao; Ai, Feixue; Zhao, Guiyan; Bi, Yanfeng; Ding, Fu; Sun, Yaguang; Xu, Zhenhe
Abstract : Monodisperse hollow microspherical YPO4 :Ln 3+ (Ln 3+ = Eu 3+ /Tb 3+ ) with diameters of around 2.5 µm have been successfully synthesised by combining a convenient homogeneous precipitation method, an ion exchange method, and a calcination process for the first time. X‐ray diffraction, Fourier transform infrared, thermogravimetric analysis, scanning electron microscopy, transmission electron microscopy, and photoluminescence spectra were used to characterise the samples. Upon ultraviolet excitation, Eu 3+ ‐ and Tb 3+ ‐doped microspherical YPO4 showed typical red and green emission, respectively, which provide potential applications in bioanalysis, future colour displays, light‐emitting devices, and so on.